“From molecular to clinic”: The pivotal role of CDC42 in pathophysiology of human papilloma virus related cancers and a correlated sensitivity of afatinib - Wei, Erdong; Li, Jiahua; Anand, Philipp; French, Lars E.; Wattad, Adam; Clanner-Engelshofen, Benjamin; Reinholz, Markus (Frontiers in Immunology, 2023)
Background: Human papilloma virus (HPV)-related cancers are global health challenge. Insufficient comprehension of these cancers has impeded the development of novel therapeutic interventions. Bioinformatics empowered us to investigate these cancers from new entry points. Methods: DNA methylation data of cervical squamous cell carcinoma (CESC) and anal squamous cell carcinoma (ASCC) were analyzed to identify the significantly altered pathways. Through analyses integrated with RNA sequencing data of genes in these pathways, genes with strongest correlation to the TNM staging of CESC was identified and their correlations with overall survival in patients were assessed. To find a potential promising drug, correlation analysis of gene expression levels and compound sensitivity was performed. In vitro experiments were conducted to validate these findings. We further performed molecular docking experiments to explain our findings. Results: Significantly altered pathways included immune, HPV infection, oxidative stress, ferroptosis and necroptosis. 10 hub genes in these pathways (PSMD11, RB1, SAE1, TAF15, TFDP1, CORO1C, JOSD1, CDC42, KPNA2 and NUP62) were identified, in which only CDC42 high expression was statistically significantly correlated with overall survival (Hazard Ratio: 1.6, P = 0.045). Afatinib was then screened out to be tested. In vitro experiments exhibited that the expression level of CDC42 was upregulated in HaCaT/A431 cells transfected with HPV E6 and E7, and the inhibitory effect of afatinib on proliferation was enhanced after transfection. CDC42-GTPase-effector interface-EGFR-afatinib was found to be a stable complex with a highest ZDOCK score of 1264.017. Conclusion: We identified CDC42 as a pivotal gene in the pathophysiology of HPV-related cancers. The upregulation of CDC42 could be a signal for afatinib treatment and the mechanism in which may be an increased affinity of EGFR to afatinib, inferred from a high stability in the quaternary complex of CDC42-GTPase-effector interface-EGFR-afatinib.